Incursão histórica pelo português arcaico: multifuncionalidade, variação e gramaticalização do pretérito mais-que-perfeito do indicativo - Sousa, Francisco José Gomes de (2025)
This study is based on the investigation of the simple and compound forms of the pluperfect indicative in data from the archaic period of the Portuguese language. Thus, this research is guided by the following objectives: to investigate the motivation for the alternation between the use of the simple and periphrastic construction; to identify the statistically significant conditioning factors of each variant; to ascertain the structural and semantic behavior of the compound verb form with regard to the grammaticalization process; and to map the different grammatical functions that are expressed by this formal arrangement. This research is supported by the theoretical assumptions of Sociofunctionalism (Tavares, 2003), an interface resulting from the marriage between Variationist Sociolinguistics (Labov, 1972, 1978, 1994 and 2001) and North American Linguistic Functionalism (Hopper; Traugott, 1993; Givón, 1995). Regarding the methodological procedures, data from the digital collection Computerized Corpus of Medieval Portuguese were examined, specifically from texts related to the 13th, 14th and 15th centuries. During the analysis, the occurrences of the variants were categorized by the following groups of factors in relation to variation: verbal type, verbal modifier, phonic salience of the verb, subject animacy and clause polarity. Regarding the grammaticalization of the periphrasis “ter” or “haver” + participle, we considered: subject argument selection, object argument selection, type of periphrastic combination, morphological marks of the participle and variation between “ter” and “haver”. In terms of multifunctionality (Coan; Lima; Sampaio, 2019), we analyzed the following functions: antepreterite, metaphorical, discursive, desiderative, conjunctive and conditional. After this procedure, the data categorization was submitted to statistical analysis by the GoldVarb X program (Sankoff; Tagliamonte; Smith, 2005), with the aim of generating relative weights that attest to the degree of relevance of each factor mentioned above, based on a multivariate analysis of the contexts and frequencies of use of the structures of the pluperfect tense. The results obtained were then correlated with empirical problems of linguistic change (Weinreich; Labov; Herzog, 2006) and with the principles of grammaticalization (Hopper, 1991). Among the results obtained, we detected: predominance of the synthetic structure in competition with the construction with ter/haver + participle for the coding of the past value of the past; statistical relevance of the linguistic conditioner “verbal type” in the variation under analysis and in the use of the simple form of the pluperfect; evidence of grammaticalization of ter/haver + participle in an early stage; prominence of the antepreterite function in both the simple and compound forms. Through this framework, we contributed to the description of phenomena linked to the Tense-Aspect-Modality complex (Givón, 1984) and 11 to the historical cartography of the linguistic system.